Unveiling the Intrinsic Catalytic Activities of Single‐Gold‐Nanoparticle‐Based Enzyme Mimetics - Hafez, Mahmoud Elsayed; Ma, Hui; Ma, Wei; Long, Yi‐Tao (Angewandte Chemie International Edition, 2019)
Gold nanoparticles (AuNPs) have been demonstrated to serve as effective nanomaterial‐based enzyme mimetics (nanozymes) for a number of enzymatic reactions under mild conditions. The intrinsic glucose oxidase and peroxidase activities of single AuNPs and Ag–Au nanohybrids, respectively, were investigated by single NP collision electrochemical measurements. A significantly high turnover number of nanozymes was obtained from individual catalytic events compared with the results from the classical, ensemble‐averaged measurements. The unusual enhancement of catalytic activity of single nanozymes is believed to originate from the high accessible surface area of monodispersed NPs and the high activities of carbon‐supported NPs during single‐particle collision at a carbon ultramicroelectrode. This work introduces a new method for the precise characterization of the intrinsic catalytic activities of nanozymes, giving further insights to the design of high‐efficiency nanomaterial catalysts. Imitation is the sincerest form of flattery: The intrinsic glucose‐oxidase‐ and peroxidase‐mimicking activities of single AuNPs and Ag–Au nanohybrids, respectively, were quantified using stochastic collision electrochemistry, providing new insights for the design of high‐efficiency, nanomaterial‐based catalysts.